Parallel search over encrypted data under attribute based encryption on the Cloud Computing. Issue 54 (October 2015) - Bouabana-Tebibel, Thouraya; Kaci, Abdellah
Abstract: Data confidentiality in the Cloud Computing is a very challenging task. Encryption is one of the most secure methods ensuring this task, and searchable encryption techniques are used to search on encrypted data without the need for decryption. But, despite this secure measure some leaks may appear when searching over data. In this article, we propose to improve confidentiality of outsourced data. We are particularly interested in reinforcing the access control on the search result, when the search is performed over encrypted data. The property behind this aspect of security is known as ACAS (Access Control Aware Search) principle. We present a hybridization of Searchable Encryption and Attribute Based Encryption techniques in order to satisfy the ACAS property. The proposed model supports a personalized and secure multi-user access to outsourced data, presenting high search performance. It deals with multi-keywords searches and is designed to speed up the search time by taking advantage of High Performance Computing, which is widely used in Cloud Computing. Two Attribute Based Encryption techniques are considered on the side of the Cloud and some conducted experiments show the efficiency of the proposed method.